Will non-conventional alternative livelihood scheme work in the framework of mangrove dominated Indian Sundarbans? - Abhijit Mitra; Arpita Saha; Maria Fernandes; Prosenjit Pramanick; Sufi a Zaman; Goutam Sengupta (Annals of Marine Science - Peertechz Publications, 2019)
The Indian Sundarbans at the apex of Bay of Bengal in the lower Gangetic delta is extremely vulnerable to climate change induced Sea Level Rise (SLR). The SLR is more than 3.00 mm yr-1 due to which the intrusion of saline water in the island takes place. The situation has posed a negative impact on the existing livelihood of the region. On this background the concept of alternative livelihood has emerged in this deltaic complex. The alternative livelihoods like oyster culture, seaweed culture, cultivation of mangrove associate species, salt tolerant rice have been discussed with the respondents and an evaluation has been carried out to identify the success of the process. It is observed that a better understanding of the ecological condition coupled with awareness generation may strengthen the concept of alternative livelihood in this mangrove dominated deltaic complex with institutional support.